Needs Analysis For Developing Digital Folktale Books In Vocational Education Context - Annim Hasibuan; Amron Zarkasih Ritonga; Zulpahri Nainggolan (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study responds to the need for innovative and culturally relevant digital learning media that engage vocational high school students. The objectives are to (1) identify students’ needs regarding content, design, and features of digital folktale books, (2) analyze students’ and teachers’ expectations toward their effective presentation, and (3) provide a conceptual foundation for developing digital folktale learning materials. Using a mixed descriptive method, data were collected through questionnaires from 30 Grade XI students and interviews with two teachers. The results show that 100% of students own smartphones and 83.3% have daily internet access. Students strongly agreed that digital folktale books should feature illustrations and animations (mean = 3.9), integrate moral and local cultural values (mean = 3.8), and be accessible via smartphones (mean = 3.8). Teachers also emphasized the need for interactive features such as quizzes and audio to improve comprehension. The findings highlight that digital folktale books can enhance motivation and contextual learning, provided that design considers accessibility and local culture. The study contributes practical insights for developing digital literature materials suited to vocational education contexts.